Filozofija, morala in etika v zdravstveni negi - Šmitek, Jana (Obzornik zdravstvene nege, 1998)
The article presents an outline of philosophy morale and ethics and their reflection in nursing care. Concepts like values, rights, duties and relationsas related to nursing care are explained. The role of philosophy in moderns management of nursing care is described. The aim of the article is to explain a document of the philosophy of nursnih care as the final result and as the guidance for practical work, through the understanding of philosophy, moral and ethical principles, values, rights, duties and their relations. Two cases of the documents of the philosophy of nursing care of a hospital ward are presented, for users and for staff.
Keywords: Abdomen; Ethics, nursing; medicinska etika; morala; morality; Morals; Nurse-patient relations; Nursing care; Patient advocacy; Philosophy, nursing; Surgery; zdravstvena nega